ANALISIS PARAMETRIK DAN NON PARAMETRIK PENGARUH KONSENTRASI SUKROSA DAN AMONIUM SULFAT TERHADAP MUTU NATA DE MELON - Amiarsi, Dwi (Informatika Pertanian, 2015)
In an effort to reduce yield losses of melon especially during period of storage, distribution, and marketing, an effective treatment is needed. A common technique is to process melon into nata de melon. The aim of the research was to determine the physical and chemical quality of nata de melon during storage. The experiment was conducted in the Laboratory of the Indonesian Center for Agricultural Post Harvest Research and Development from July 2010 until February 2011. The design used was a completely randomized (CRD) factorial design, with two factors i.e. sucrose (6%; 8%; and 10%) and ammonium sulfate (0%, 0.4%, 0.6%, and 0.8%) with two replications. The data was analyzed using parametric and non-parametric analyses. The results showed that 8% sucrose treatment was more effective in increasing yield, thickness, fiber content, firmness and flavor than other sucrose concentrations in nata de melon production. Additional treatment of ammonium sulfate 0.8% was more effective in increasing yield, thickness, fiber content, and elasticity compared to other concentrations of ammonium sulfate in nata de melon production. In general, a treatment combination of 8% sucrose and 0.6% ammonium sulfate can produce nata de melon better. Processing into nata de melon may prolong shelf life and increase the added value of melon.